STRATEGIES FOR MULTICULTURAL COMMUNICATION: A STUDY OF INDONESIAN POSTGRADUATE STUDENTS - Mia Rahmawati Yuwita (Universitas Pakuan, 2023)
This study focuses on the multicultural communication strategies employed by Indonesian postgraduate students during their study abroad experience at a university in Melbourne, Australia. Multicultural communication, as the main focus of this research, refers to communication between participants from different lingua-cultural backgrounds or nations, where their different conceptualizations and perspectives may lead to potential miscommunication. To achieve the research objective successfully, a qualitative method, specifically a semi-structured interview, was adopted to collect the data. 4 Indonesian postgraduate students who studied abroad in Melbourne, Australia were interviewed and asked about their cross-cultural misunderstanding experience during their sojourn period in Australia. They were also asked how they negotiated meaning and overcame language barriers when they communicated with local Australians or other international students. The collected data were analyzed and discussed in reference to strategies for multicultural communication theoretical framework. The findings of this study demonstrate that the respondents implemented a range of strategies to achieve successful intercultural communication, and the observation of others was deemed as one of the most effective methods. The outcomes of this research could provide a useful reference for students who plan to study abroad, especially in Melbourne, Australia, on the various strategies they can use to have effective communication across cultures.